POLA IMPELEMENTASI PENDIDIKAN ISLAM DI ERA DIGITAL DALAM PENGUATAN PELAJAR PANCASILA DI SMPN 2 KALANGANYAR - Nisa Nafisha Aulia; Wasehudin Wasehudin; Habudin Habudin; Mufti Ali; Fandy Adpen Lazzavietamsi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The merdeka curriculum mandates teachers to strengthen the profile of Pancasila students. The basic character values of Pancasila must be reflected in students, namely the values of faith and devotion to God Almighty, working together, global diversity, critical reasoning, independence and creativity. This research aims to explore patterns of implementing Islamic education in the digital era in empowering Pancasila students. This study is qualitative research using a case study method at SMPN 2 Kalanganyar. Interview techniques, documentation studies and observations were used to obtain data in this research. Data were analyzed using the Miles and Huberman model, namely data collection, data presentation, drawing conclusions and verification. The research results show that the pattern of implementing Islamic education in the digital era in facing the strengthening of Pancasila students at SMPN 2 Kalanganyar is carried out through planning, implementation and evaluation. The planning process is carried out by including the dimensions of the Pancasila student profile in terms of achievement and learning objectives. Project and problem-based learning models are used to strengthen the Pancasila student profile. Meanwhile, in the evaluation pattern, apart from measuring understanding of PAI material, PAI teachers also use instruments to measure the profile of Pancasila students such as non-test instruments.